THE CENTER AND THE PERIPHERY – CROATIA IN THE REALM OF KING MATTHIAS CORVINUS - Grgin, Borislav (1998)
The main task of this paper is to evaluate the impact of the king on local political development and on political and military issues connected with the Ottoman threat, as well as the role of Croatia in the kingdom’ s anti-Ottoman defense system. The rivalry with Venice and the Empire over eastern Adriatic is also taken into account.